PERBEDAAN HASIL BELAJAR STATISTIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DAN TPS PADA SISWA KELAS X - Amalia, Poppy; Surya, Edy (Kreano, Jurnal Matematika Kreatif-Inovatif, 2017)
ABSTRACTThis research aims to demonstrate that the results of the statistical learning by applying cooperative learning model NHT better than TPS in class X SMK. This research was quasi experimental. The populationof the research was all students of class X semester II. Sampling was done by simple random sampling by taking two classes of sixth grade were randomly ie class X TKR-1 as the experimental class A and class X TKR-3 as the experimental class B, where the experimental class A implement cooperative learning model NHT and class experiment and implement cooperative learning model TPS. Calculation results obtained tcalculate = 3.32447 and ttable= 1.67078 so tcalculate>ttablethe real level of 0.05, the hypothesis was accepted. Thus we concluded that the results of a statistical study between cooperative learning model NHT better than TPS in class X.Keyword: the result of the study, nht, tps